End-Cycle Sow Carcass Condemnation in a French Slaughterhouse - Decaudin, Pierre-Yves; Raboisson, Didier; Waret-Szkuta, Agnès (Frontiers in Veterinary Science, 2017)
Surveillance at an abattoir allows all animals or carcasses that present a potential public health risk to be withdrawn from the human food chain. Whole-carcass condemnation results in important economic losses, not only for the producer but also for other participants in the meat industry. Access to the personal electronic database of an abattoir in France enabled us to run logistic regression models to investigate the risk factors for whole-carcass condemnation of end-cycle sows in that abattoir. When end-cycle sows that were slaughtered and eviscerated between 22/06/2015 and 08/12/2015 (185 days) were considered (n=19,866), the results highlighted the importance of the total theoretical time off feed, which represents the fasting period from leaving the farm of origin to the time of slaughter (including transportation and waiting time at the abattoir). Each 10-hour increase in the theoretical time off feed was associated with a 31% greater likelihood of whole-carcass condemnation (OR=1.31, CI 95% [1.27; 1.34]), and a 10 kg increase in carcass weight before refrigeration was associated with a 23% lower likelihood of carcass condemnation (OR=0.77, CI 95% [0.75; 0.78]). The results also indicate the importance of the producer group that the farmer belonged to (p<0.01). A relatively small number of variables was available in the actual database to study the relevant risk factors for whole-carcass condemnation associated with or without diseases at the farm of origin. This derives partly from the fact that traceability at the abattoir in France is done per batch rather than individually for pigs; further, limited information is available at the farm level. An investigation of the reasons for whole-carcass condemnation could have been informative; however, it was not feasible in a reasonable timeframe because the data were not saved in a database in a systematic way. Some of the difficulties encountered in this study should soon be alleviated by using the meat inspection information system software for collecting livestock meat inspection data. Implemented recently by the French ministry of agriculture, this new tool should allow for broader perspectives in swine surveillance.